2023
DOI: 10.3390/ejihpe13030041
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Skills (Competence) and Coping Strategies in Adolescent Depression

Abstract: Depression is a state of low mood that can lead to several negative outcomes on thoughts, emotions, behaviors, and even physical state. With that in mind, it is important to detect individuals at risk of developing depressive symptoms early and identify protective factors. During the COVID-19 pandemic, adolescents emerged as one of the most vulnerable groups, with deteriorated anxiety and depression due to imposed social isolation, reduced social activities, and concerns over household status, health, and peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Ultimately, we must also consider that women who use more emotion-focused coping may also require support due to increased emotional burdens during and after the pandemic. This is also corroborated by literature, which stated that females reported significantly elevated levels of stress and psychological problems, such as depression and anxiety during the current COVID-19 pandemic [ 4 , 79 ], and emotion-focused coping reduces negative emotions associated with the COVID-19 pandemic as the stressor [ 74 ]. Men use more problem-focused coping while women use more emotion-focused coping and social support seeking [ 80 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Ultimately, we must also consider that women who use more emotion-focused coping may also require support due to increased emotional burdens during and after the pandemic. This is also corroborated by literature, which stated that females reported significantly elevated levels of stress and psychological problems, such as depression and anxiety during the current COVID-19 pandemic [ 4 , 79 ], and emotion-focused coping reduces negative emotions associated with the COVID-19 pandemic as the stressor [ 74 ]. Men use more problem-focused coping while women use more emotion-focused coping and social support seeking [ 80 ].…”
Section: Discussionsupporting
confidence: 77%
“…The research also found a higher association between women and emotion-focused coping strategies. Females scored higher on emotion-focused coping, which highlighted gender differences in a study conducted in Croatia [ 74 ]. Conversely, the findings contradict a previous study in China, which reports that women are less likely to choose emotion-focused coping strategies during the COVID-19 pandemic [ 16 ].…”
Section: Discussionmentioning
confidence: 87%
“…This indicates that high emotional intelligence not only encourages better coping with stress, but also forms a general positive attitude towards the stressful situation itself. It does not limit the individual in the choice of coping strategies, but encourages the search for the most optimal coping strategies [23] . Emotional intelligence plays a significant role in experiencing a crisis, because a person in a stressful situation looks for solutions or feels discomfort trying to reduce the significance of the situation, distance himself/herself from it [24] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Identifying triggers is important for the individual to understand his or her own emotions [27]. Naming emotions: It is the process of trying to describe one's emotions by naming them [28]. Keeping a diary: It is especially important to write down our feelings to recognize them [29].…”
Section: Emotional Intelligencementioning
confidence: 99%